Balance Identification to Reduce the Risk of Falls in the Elderly - Norlinta, Siti Nadhir Ollin; Irfan, Muhammad (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Balance disorders are a major factor in influencing some elderly disability rates in Indonesia. Especially the incidence of falls that can cause a decrease in quality of life. Therefore, it is important to take preventive measures in the form of identifying the risk of falling in the elderly group with the Time Up and Go Test (TUG) balance test. Methods: A quantitative study with a descriptive cross-sectional approach was used in the Tridadi elderly group, Sleman Regency, Special Region of Yogyakarta. The TUG test results were grouped into two; high risk of falling if the respondent completed the TUG test in more than 13.5 seconds and the normal category if the respondent was able to do the test in less than 13.5 seconds. The data were analyzed and presented based on a frequency table with sampling using the purposive sampling method. Results: From a total of 29 Tridadi elderly group populations, the average total test duration was 10.68 seconds. Male respondents were on average faster in completing the test than female respondents 9.3:10.84. A high risk of falling was found in 4 out of 29 respondents (13%) all of whom were female with an age range of 48-69 years. Conclusion: The level of risk of falling in the Tridadi elderly group shows that the female elderly group tends to have a higher risk of falling with a longer TUG test duration than men. By identifying the risk of falling figures, further steps need to be taken related to the analysis of risk factors and preventive and rehabilitative steps in the population at risk of falling.